Oxytocin and pain perception: from animal models to human research - Boll, Sabrina; Herpertz, Sabine; Grinevich, Valéry (Neuroscience, 2018)
An accumulating body of evidence suggests that the hypothalamic neuropeptide oxytocin (OT) has a modulatory effect on pain processing. Particularly strong evidence comes from animal models. Here, we review recent advances in animal research on the analgesic effects of OT and discuss possible target sites of OT within descending and ascending pain pathways in the brain. In addition to the spinal cord being a direct target of the neuropeptide, OT has also been shown to modulate the neuronal activity of limbic and cortical brain regions, which play a major role in the cognitive and emotional processing of pain. Human studies investigating the influence of OT on pain perception are less numerous and have revealed less consistent results. The human literature is therefore scanned thoroughly and different approaches to study the effects of OT on pain perception in humans are discussed. Moreover, we also address how OT might alleviate pain by influencing socio-emotional components in humans. We conclude that further investigating specific OT and OT-sensitive circuits, which modulate pain processing especially in primates, will improve our understanding of OT-analgesic effects. In human research, the increased use of neuroimaging and autonomic measures might help to bridge the gap to animal studies.
Available online 28 September 2017
Gesehen am 11.09.2018